IMPROVING RESIDENTIAL BUILDINGS IN UZBEKISTAN THROUGH ENERGY-EFFICIENT SOLUTIONS - Akhmedova Firuza Ma’rufjonovna (Modern American Journals, 2025)
This article discusses the methods of natural cooling of residential buildings during the hot period of the year. These methods have been used since past times in the geographical regions of Central Asia, and research conducted on this topic in foreign countries is also presented. Furthermore, it is shown how the natural cooling techniques used in past times can be applied to modern low-rise and multi-story residential buildings.
Keywords: Badgir, wind-catcher, tabadan, tunnel, geothermal energy, north